Southern Sovereignty: Tasmania and New Zealand in the Southern Ocean 1894-1897 - Kellaway, RG (Australian Historical Asociation, 2011)
In October 1890, the Tasmanian House of Assembly overwhelmingly rejected a plan to transfer Macquarie Island from Tasmania to New Zealand. While this should have been the end of the matter, the government of New Zealand continued to put forward propositions for gaining control of the island. The 1894 plan called for a re-opening of negotiations for the formal transfer of territory. Subsequent approaches in 1895 and 1897 suggested a leasing arrangement in which New Zealand would administer the island but where formal sovereignty would remain with Tasmania. All proposals were rejected.This paper examines the reasons behind the continuing appearance and rejection of transper proposals. Three issues appear to be at work. One was New Zealand's concern about the impossibility of Tasmania exercising effective control, its remote dependancy and the threat that this posed to their interests in the Southern Ocean. Another involved somewhat implausible ambitions by entrepreneurs in both countries to use Macquarie Island as a base for the development of Southern Ocean whaling; while the third and more rational reason involved the possibility of using the Macquaries as a stepping stone to the Antarctic. Exploration projects were becoming more prominent, and an economic imperative was foremost in many of these schemes.